Estratégias adotadas pelos agricultores familiares na escolha dos canais de comercialização no setor de frutas, legumes e verduras do município de Itaqui - RS - Possani, Laura (2016)
The world population has been changing their eating habits in an attempt to improve their quality of life. The increase in the consumption of foods such as fruits and vegetables has directly influenced the lives of the producers. Studies show that most of these products are produced by family farmers, similarly to what happens in the municipality of Itaqui-RS. However, recent local studies have shown that these farmers find it difficult to insert themselves effectively in supermarket supply chains. The key question of this research is to understand how these producers are organized to meet the current demands and what are the main factors that influence the choice of the commercialization channels that they access. Semi-structured interviews were carried out with 5 family farmers who have access to more than one commercialization channel, thus making it possible to visualize the elements of choice. As a conceptual basis, the theory of Transaction Cost Economics (ECT) was chosen to support interpretations of how farmers organize and how they regulate their transactions. In the study, the presence of the attributes of the transactions was verified, the frequency being the most relevant attribute for all the interviewees, since their presence generates confidence between the parties. The analysis of the transactions allowed to conclude that the farmers choose the commercialization channels based on the attributes of the ECT, using them to govern their transactions in a satisfactory way. It is concluded that the main factors considered by the producers to choose these channels is the confidence (generated by the frequency in which they occur) and the price of the products.